2019
DOI: 10.1029/2018jc014655
|View full text |Cite
|
Sign up to set email alerts
|

Meridional Heat and Salt Transport Across the Subantarctic Front by Cold‐Core Eddies

Abstract: Mesoscale eddies are ubiquitous in the Southern Ocean particularly in regions where the Antarctic Circumpolar Current interacts with topography. Eddies play a critical role in the meridional transport of heat and salt across the Antarctic Circumpolar Current. However, observations of the heat and salt content of eddies are extremely rare. Here we present new observations that characterize the three‐dimensional structure of a cyclonic (cold‐core) eddy generated at the Subantarctic Front south of Tasmania. Autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(92 citation statements)
references
References 48 publications
7
75
1
Order By: Relevance
“…5) and nitrate and silicate concentrations were 22 and silicate was 3.3 mM respectively, all typical of polar waters located further south of the northern extension of the SAF (Moreau et al 2017;Patel et al 2019). Satellite analysis revealed that the eddy had formed in early February 2016 and moved northward ,1.28 of latitude at the time of sampling (Patel et al 2019). Satellite analysis of the eddy also revealed that it had a lower chlorophyll concentration than surrounding waters, consistent with its development further south in less-productive polar waters (Fig.…”
Section: Hydrographymentioning
confidence: 93%
See 3 more Smart Citations
“…5) and nitrate and silicate concentrations were 22 and silicate was 3.3 mM respectively, all typical of polar waters located further south of the northern extension of the SAF (Moreau et al 2017;Patel et al 2019). Satellite analysis revealed that the eddy had formed in early February 2016 and moved northward ,1.28 of latitude at the time of sampling (Patel et al 2019). Satellite analysis of the eddy also revealed that it had a lower chlorophyll concentration than surrounding waters, consistent with its development further south in less-productive polar waters (Fig.…”
Section: Hydrographymentioning
confidence: 93%
“…The eddy was ,190 km in diameter and was a stable feature that had formed in mid-February 2016, ,1.28 further south of the sampling site near the SAF (Moreau et al 2017). After formation, the eddy moved slowly northward across the northern extension of the SAF with a rotation speed of 0.527 rad day À1 (Moreau et al 2017;Patel et al 2019). The biogeochemical properties of this eddy differ from external waters (Moreau et al 2017;Patel et al 2019).…”
Section: Sampling Sitesmentioning
confidence: 94%
See 2 more Smart Citations
“…These observations of large fluxes over the SO mesoscale eddies might be governed by the sea surface temperature anomaly arising from the ocean polar front in the SO as well as lifetime and evolution stage of the ocean eddy. During the sampling, the cold eddy had reached past its mature stage and had entered its decay phase impacting its amplitude (Patel et al, ). The warm eddy, however, was a short‐lived eddy and shifted its center quickly as per the altimetry observations.…”
Section: Discussionmentioning
confidence: 99%